The Influence of Live Streaming and Discounts on Purchase Decisions on TikTok Shop in Karawang Regency - Martien, Nita; Isyanto, Puji; Sumarni, Neni (JEM17: Jurnal Ekonomi Manajemen, 2025)
This study aims to analyze the influence of live streaming and discounts on consumer purchasing decisions on the TikTok Shop platform in Karawang Regency. The background of this research is the growing use of TikTok as an interactive promotional medium that utilizes the live streaming feature to sell products directly. In addition, discount strategies are considered effective in attracting consumer attention and influencing purchasing decisions. This study adopts a quantitative approach with purposive sampling techniques involving 125 respondents who are active TikTok Shop users. Data was collected through questionnaires and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method with the SmartPLS 4 application. The results indicate that live streaming has a significant influence on purchasing decisions, as the interactivity and clarity of information delivered by the host can enhance consumer trust and perceived product quality. Discounts also show a significant effect, particularly when price reductions are applied to products that are of interest to consumers. These findings suggest that both live streaming and discounts play important roles in encouraging consumer purchases. Keywords : Live Streaming, Diskon, Keputusan Pembelian, TikTok Shop